2016
DOI: 10.1088/0029-5515/56/12/126014
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the thermomechanical behaviour of the tungsten first wall in HiPER laser fusion scenarios

Abstract: The behaviour of a tungsten first wall is studied under the irradiation conditions predicted for the different operational scenarios of the European laser fusion project HiPER, which is based on direct drive targets and an evacuated dry wall chamber. The scenarios correspond to different stages in the development of a nuclear fusion reactor, from proof of principle (bunch mode facility) to economic feasibility (pre-commercial power plant). This work constitutes a quantitative study to evaluate first wall perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
22

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 52 publications
(110 reference statements)
0
17
0
22
Order By: Relevance
“…It has the best proprieties with respect to thermo-mechanical stresses and hydrogen retention. However, it was demonstrated that a coarse-grained tungsten is not sufficiently resistant to the radiation loads [30,31]. It cannot withstand more than 1000 laser shots with a fusion energy release of 250 MJ.…”
Section: Inertial Fusion Energy Research In Europementioning
confidence: 99%
See 1 more Smart Citation
“…It has the best proprieties with respect to thermo-mechanical stresses and hydrogen retention. However, it was demonstrated that a coarse-grained tungsten is not sufficiently resistant to the radiation loads [30,31]. It cannot withstand more than 1000 laser shots with a fusion energy release of 250 MJ.…”
Section: Inertial Fusion Energy Research In Europementioning
confidence: 99%
“…Much more promising properties are demonstrated by a nano-structured tungsten. Its performance has been studied with multi-scale numerical simulations and experiments showing that neutron-induced vacancies are readily attached to the grain boundaries and effectively annealed with interstitials at temperatures about 600 K [31,32].…”
Section: Inertial Fusion Energy Research In Europementioning
confidence: 99%
“…4 associated properties [23]. According to literature, the base temperature as estimated by finite element methods at the PFM surface of the European designed of a nuclear fusion reactor can reach up to 900 K [24]. Therefore, the study of the thermal stability of NW is a key point, since at this temperature grain growth should be excluded for a proper performance of the reactor.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Actualmente, el wolframio (W) es considerado como una de las alternativas más robustas para cumplir la función de PFM, debido a su elevado punto de fusión (3695 K) y su conductividad térmica (aproximadamente 160 W m -1 K -1 ), bajo coeficiente de sputtering y baja retención de tritio [12,14,[26][27][28][29]. Sin embargo, las condiciones de operación (típicamente, de flujos de partículas superiores a 10 19 cm -2 s -1 ) suponen todo un reto para la aplicación de este material, tanto por consideraciones termomecánicas [30] como atomísticas, siendo estas últimas de mayor relevancia al ser responsables de una miríada de efectos perjudiciales, como agrietamiento, hinchamiento, exfoliación, y, bajo ciertas condiciones, el crecimiento de nanoestructuras superficiales de baja densidad conocidas globalmente como "fuzz" [31][32][33][34][35][36]. Estos efectos atomísticos tienen su origen en la nucleación de especies ligeras, productos de la reacción de fusión (tales como hidrógeno, deuterio, tritio y helio) en defectos puntuales, capaces de erosionar la superficie del PFM, o de implantarse en su seno, donde tienden a nuclear en otros defectos [29,31,[37][38][39][40].…”
Section: Motivación De La Tesisunclassified
“…El desarrollo de centrales de fusión nuclear se encuentra seriamente limitado por diversos factores [1,3,12], si bien en las últimas décadas la comunidad científica ha llevado a cabo importantes esfuerzos para superar estos problemas, especialmente en las principales alternativas consideradas: la fusión nuclear por confinamiento magnético (MCF) y por confinamiento inercial (ICF). Uno de estos factores limitantes es la ausencia de materiales capaces de soportar la exposición al plasma [3,12,30,226,227] y las duras condiciones de irradiación esperadas, especialmente la alta temperatura y el daño atomístico causado por los eventos de irradiación pulsados en MCF e ICF [227,228]. Aunque el empleo de W como PFM resulta atractivo debido a sus propiedades termomecánicas, la nucleación de especies ligeras (como H y He) en defectos puntuales da lugar a la formación de defectos atomísticos responsables de un gran número de efectos perjudiciales [31,35,36].…”
Section: Introductionunclassified